Financial systems, corporate investment in innovation, and venture capital - Bartzokas, Anthony, 1962-; Mani, Sunil (Cheltenham : Edward Elgar, 2004)
This book examines the role of venture capital institutions in financing technology-based ventures both in developed and developing countries. It also explores that part of venture capital activity which is hitherto vastly under-researched; namely the ability of venture capital institutions to render a whole host of value-added support functions.
Formerly CIP
Includes bibliographic references and index.
gau 17/06/14
Loans
Keywords: Venture capital; High technology industries -- Capital investments; High technology industries -- Capital investments -- Developing countries; Financial systems; Corporate investment